2001
DOI: 10.1007/3-540-45508-6_7
|View full text |Cite
|
Sign up to set email alerts
|

A Practical Model for VBR Video Traffic with Applications

Abstract: Video traffic compressed with variable bit rate coding scheme is known to possess high variations and multiple time scale characteristics. This property makes parsimonious video modeling a difficult task. A possible way of describing this traffic is via self-similar models, which also produce high variations on many time scales. However, these are general traffic models and do not represent many important characteristics of video. In this paper we show that video traffic has well-separable time scales. Based o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2004
2004
2009
2009

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 16 publications
(22 reference statements)
0
3
0
Order By: Relevance
“…Additionally, several authors suggest the concept of an activity regime, which is located in between the scene and the GoP layers [1,2,4]. For the video traces employed, Baey observes that only a small fraction of a video stream corresponding to high activity is responsible for delays, while the major part can be transmitted without delays (low activity phase).…”
Section: Video Trafficmentioning
confidence: 99%
“…Additionally, several authors suggest the concept of an activity regime, which is located in between the scene and the GoP layers [1,2,4]. For the video traces employed, Baey observes that only a small fraction of a video stream corresponding to high activity is responsible for delays, while the major part can be transmitted without delays (low activity phase).…”
Section: Video Trafficmentioning
confidence: 99%
“…It was observed that the bandwidth requirements of streamed video remains relatively constant in 10-30 second intervals, but can vary significantly between these intervals [19] due to factors such as variable rate compression. Our experimental results in Section V reflect this observation and demonstrate the performance of our protocol both for the case when the demands remain constant, and when the sources change them.…”
Section: Inelastic Traffic Demandsmentioning
confidence: 99%
“…Furthermore, we recognized that each video sequence differs from others, which makes modeling of these types of traffic sources very difficult. Several researchers took our traces and tried to build traffic models from the traces, e.g., [3,13]. We encoded each video sequence with different settings such as the quality or the resulting bit rate to offer other researchers a large library satisfying their needs.…”
Section: Introductionmentioning
confidence: 99%